2015
DOI: 10.1186/s12888-015-0419-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of clinical characteristics between adolescent males and females with eating disorders

Abstract: BackgroundEating disorders (ED) are serious disorders that have a negative impact on both the psychological and the physiological well-being of the afflicted. Despite the fact that ED affect both genders, males are often underrepresented in research and when included the sample sizes are often too small for separate analyses. Consequently we have an unclear and sometimes contradictory picture of the clinical characteristics of males with ED. The aim of the present study was to improve our understanding of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 39 publications
1
43
1
Order By: Relevance
“…Approximately one third of children with EDs report having abdominal complaints, including constipation, bloating, abdominal pain, and dyspepsia (Basso et al, ) (see Table ). Basso et al () reported the rate of celiac disease in a sample of children (81% female) with AN (0.6%) (Basso et al, ) to be similar to the general population (Green & Cellier, ), but Welch, Ghaderi, and Swenne () examined a larger sample of children with different types of EDs and found a rate of AN or atypical AN that was four times greater in girls (2.4%) and absent in boys (Welch et al, ). Similarly, Karwautz et al () examined a sample of children with celiac disease and found that the rates of EDs for females (4.8% with a history of ED; 3.9% with a current ED; [Karwautz et al, ]) were substantially higher than the general population (AN 0.3%; BN 1%; BED 1%) (Hoek & van Hoeken, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately one third of children with EDs report having abdominal complaints, including constipation, bloating, abdominal pain, and dyspepsia (Basso et al, ) (see Table ). Basso et al () reported the rate of celiac disease in a sample of children (81% female) with AN (0.6%) (Basso et al, ) to be similar to the general population (Green & Cellier, ), but Welch, Ghaderi, and Swenne () examined a larger sample of children with different types of EDs and found a rate of AN or atypical AN that was four times greater in girls (2.4%) and absent in boys (Welch et al, ). Similarly, Karwautz et al () examined a sample of children with celiac disease and found that the rates of EDs for females (4.8% with a history of ED; 3.9% with a current ED; [Karwautz et al, ]) were substantially higher than the general population (AN 0.3%; BN 1%; BED 1%) (Hoek & van Hoeken, ).…”
Section: Resultsmentioning
confidence: 99%
“…Celiac disease typically preceded the onset of disordered eating and a diagnosable ED in the majority of cases (85.7%), with an average of 9.87 years between the onset of celiac disease and the onset of eating pathology (Karwautz et al, ). Karwautz et al () and Wagner et al () found evidence that celiac disease started prior to the onset of disordered eating, but Basso et al (), Quick et al (), and Welch et al () did not provide data on the order of onset. Overall, children with celiac disease have a greater risk for developing EDs and disordered eating than the general population and the risk is predominant in females.…”
Section: Resultsmentioning
confidence: 99%
“…Because research on eating disorders has historically focused on women, the nosology of eating disorders has evolved based on female symptom profiles (Anderson & Bulik, ) and normative data on men are lacking (see Figure S1 for lifetime prevalence of eating disorders by sex). Evidence indicates that, when diagnosed with eating disorders, men and women often differ in clinical characteristics (Núñez‐Navarro et al, ; Welch, Ghaderi, & Swenne, ), although psychiatric comorbidities appear common across gender (Ulfvebrand, Birgegård, Norring, Högdahl, & von Hausswolff‐Juhlin, ). Available evidence also suggests that men may be less likely to seek treatment (Striegel, Bedrosian, Wang, & Schwartz, ), less likely to be diagnosed with an eating disorder even when presenting with identical symptoms as women (Currin, Schmidt, & Waller, ), and less likely to access treatment even with similar clinical severity (Austin et al, ).…”
Section: Truth 5: Eating Disorders Affect People Of All Genders Agesmentioning
confidence: 99%
“…Of note, few studies have distinguished between ED diagnostic groups when assessing sex differences. While evidence suggests that females with AN, BN, and BED report greater severity than males across several cognitive and behavioral ED domains (Dahlgren et al, 2017; Darcy et al, ; Shingleton, Thompson‐Brenner, Thompson, Pratt, & Franko, ), findings in AN have not been entirely consistent (Welch, Ghaderi, & Swenne, ).…”
Section: Introductionmentioning
confidence: 99%